2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610130
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular junction in a microfluidic device

Abstract: Malfunctions at the site of neuromuscular junction (NMJ) of post-injuries or diseases are major barriers to recovery of function. The ability to efficiently derive motor neurons (MN) from embryonic stem cells has indicated promise toward the development of new therapies in increasing functional outcomes post injury. Recent advances in micro-technologies have provided advanced culture platforms allowing compartmentalization of sub-cellular components of neurons. In this study, we combined these advances in scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Concerning PN-modelling, several methods were developed to generate contractile myotubes on lab-on-chip devices (i.e., [9][10][11]). But more relevantly, numerous protocols focused on mimicking PN networks (allowing neuromuscular junction (NMJ) formation) using muscle-derived cells (i.e, [12]), spinal cord slices (i.e., [13]), stem cells (i.e., [14,15]), and induced pluripotent stem cells (i.e., [16]), and in some of these, muscle activity was also analyzed (i.e., [11,[16][17][18]). However, none of these methods monitor the molecular events that occur in both muscle cells and MN after a PN axotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning PN-modelling, several methods were developed to generate contractile myotubes on lab-on-chip devices (i.e., [9][10][11]). But more relevantly, numerous protocols focused on mimicking PN networks (allowing neuromuscular junction (NMJ) formation) using muscle-derived cells (i.e, [12]), spinal cord slices (i.e., [13]), stem cells (i.e., [14,15]), and induced pluripotent stem cells (i.e., [16]), and in some of these, muscle activity was also analyzed (i.e., [11,[16][17][18]). However, none of these methods monitor the molecular events that occur in both muscle cells and MN after a PN axotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Recordings of electrical activity of the motor neurons were recorded on day 8,15,22,28,35,42,49,56, 63 and 70 days in vitro (DIV). Each recording was 4 minutes long at 10 000Hz, and was made at least 24 hours after media replacement.…”
Section: In Vitro Electrophysiology and Antigenic Profile Of Mn Networkmentioning
confidence: 99%
“…Indeed, a number of studies have demonstrated the applicability of various bioengineering methods for creating muscle-neuron co-cultures, including functional NMJs in vitro. [15][16][17][18][19][20][21] In the present study, we model functional human NMJs by compartmentalized culture of iPS cell-derived MN pseudo-organoids and myotubes in a differentially perturbable multi-nodal microfluidic chip and demonstrate that NMJ function can be validated through monosynaptic retrograde tracing using a designer pseudotyped ΔG-rabies virus (RV).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on mimicking neuromuscular junctions using micro-fluidic devices revealed that this technology could closely recapitulate ALS conditions in a dish. [79,80] …”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%